The significance of salivary cationic antimicrobial peptides in caries risk assessment in children: A literature review - Stojković Branislava B.; Igić Marija Lj; Tričković-Janjić Olivera R.; Igić Ana N.; Veličković Zorana M.; Stojanović Simona M.; Petrović Milica S.; Kostić Miloš S.; Živković Nikola D.; Spasić Milan S. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: Caries risk assessment is the essential step in the modern clinical approach to caries management. It is a basic prerequisite for the development of preventive measures and strategies for the primary prevention of caries. Its reliability is conditioned by the knowledge of relevant caries risk factors - indicators and predictors of caries. Aim: After reviewing the available literature, the paperwork aimed to analyse the importance of salivary levels of cationic antimicrobial peptides as indicators and predictors of caries in children, i.e., their possible role in caries risk assessment in children. Material and methods: The analysis included original articles in English which studied the association of salivary levels of cationic antimicrobial peptides with caries in children. Three databases were selected: PubMed, Scopus, and Web of Science, and the search was performed using the following keywords: saliva cationic peptides /antimicrobial peptides /AMP/ defensins/ cathelicidin/histatin/statherin/adrenomedullin/azurocidin AND dental caries AND children/children age. Conclusion: Cationic antimicrobial peptides could be important caries risk indicators in children. Unfortunately, there is currently no reliable evidence of their caries predictive value. Well-designed cross-sectional and long-term longitudinal studies are still required to clarify the significance of salivary cationic antimicrobial peptides as reliable caries risk indicators and caries predictors in children. At the same time, this would define their significance as caries risk biomarkers and their potential application in caries risk assessment in children.